Оцінка ефективності застосування фізіотерапії при тривожно-депресивних станах хворих на хронічні хвороби = Evaluation of the effectiveness of physiotherapy in the anxiety-depression patients with chronic diseases - Lomeyko, S M; Chuhrayev, M V; Volodymyrov, A O; Unichenko, A V; Zukow, W (Journal of Education, Health and Sport, 2015)
Lomeyko S M, Chuhrayev M V, Volodymyrov A O, Unichenko A V, Zukow W. Оцінка ефективності застосування фізіотерапії при тривожно-депресивних станах хворих на хронічні хвороби = Evaluation of the effectiveness of physiotherapy in the anxiety-depression patients with chronic diseases. Journal of Education, Health and Sport. 2015;5(6):183-190. ISSN 2391-8306. DOI 10.5281/zenodo.18462 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A183-190 https://pbn.nauka.gov.pl/works/564726 http://dx.doi.org/10.5281/zenodo.18462 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 05.06.2015. УДК 616.711: 612.821+615.831.8 Оцінка ефективності застосування фізіотерапії при тривожно-депресивних станах хворих на хронічні хвороби Evaluation of the effectiveness of physiotherapy in the anxiety-depression patients with chronic diseases С. М. Ломейко1, М. В. Чухраєв2, А. О. Володимиров2, А. В. Уніченко2, W. Zukow3 S M Lomeyko1, M V Chuhrayev2, A O Volodymyrov2, A V Unichenko2, W Zukow3 1 Санаторій «Трускавець», Трускавець, Україна 2 Науково-методичний центр «Медінтех», Київ, Україна 3 Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska 1 Sanatorium "Truskavets", Truskavets, Ukraine 2 Scientific center "MEDINTEKh", Kyiv, Ukraine 3 Kazimierz Wielki University, Bydgoszcz, Poland Резюме Представлені результати дослідження ефективності застосування низько інтенсивної резонансної фізіотерапії та синглетно-кисневої терапії в комплексній програмі медичної реабілітації тривожно-депресивних станів хворих на хронічні хвороби. Summary The results of the study the efficacy of low intensive physiotherapy and resonance singlet-oxygen therapy in a comprehensive program of medical rehabilitation hidden depression in patients with diabetes mellitus. Ключові слова: фізіотерапія, тривожно-депресивних стан, хвори на хронічні хвороби. Key words: physiotherapy, anxiety-depression, patients with chronic diseases.